Pengaruh Kemitraan, Dukungan Lingkungan Eksternal, dan Inovasi Terbuka terhadap Kompetensi Digital Pelaku UMKM Kuliner - Widyanti, Oktarina Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to examine the influence of partnerships, external environmental support, and open innovation on the digital competence of culinary MSME actors in Bogor City. The research is motivated by the low adoption of digital technology in the culinary MSME sector, despite the proven potential of digitalization to significantly enhance operational efficiency and market reach. Employing a quantitative approach with an explanatory design, this study involved 154 culinary MSME owners actively using digital platforms, selected through convenience sampling. The research instrument was developed using a five-point Likert scale and consisted of 51 indicators representing four main constructs. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all independent variables have a positive and significant effect on digital competence: partnership (β=0.518; p<0.001), external support (β=0.231; p=0.013), and open innovation (β=0.177; p=0.032). The R-square value of 0.735 indicates that the model has a strong explanatory power for digital competence. These results highlight the importance of strategic collaboration, ecosystem engagement, and access to innovative external resources in shaping MSMEs’ digital readiness. The study contributes theoretically to the literature on innovation and digital transformation, and provides practical implications for policymakers and MSME practitioners in formulating collaborative digitalization strategies. It recommends strengthening cross-sector partnerships and facilitating open innovation as key drivers for enhancing the sustainability of MSMEs in the digital economy era.